Злые стволы: [роман] / Андрей Ильин - Ильин Андрей Александрович (Черная кошка, 1998)
Экземпляры: РБ (20221222) / Инвентарный номер: 64551 / Цена: 10.00 / Авт.знак: И 46 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6